Rekonstruksi epistemologi pendidikan islam: Integrasi nilai-nilai filsafat islam dalam pengembangan kurikulum multikultural era digital - Mubarok, Muhammad Syafi’ul (Maliki Interdisciplinary Journal, 2025)
Reconstructing the epistemology of Islamic education has become an urgent necessity in responding to the digital era, which is marked by shifts in how knowledge is acquired, validated, and distributed. The normative and historical sources of Islamic epistemology affirm that knowledge must be built through the integration of revelation, reason, and human experience. In the context of multicultural education, the values of justice, humanity, and rationality are essential for developing curricula that are responsive to cultural diversity and global challenges. The paradigm shift in Islamic education demands renewal in its ontological, epistemological, and axiological dimensions so that educational institutions can adapt to technological and social dynamics. This article employs a conceptual approach to analyze the foundations of Islamic epistemology, the core values of Islamic philosophy, and the urgency of curriculum reconstruction in the digital era. The analysis indicates that Islamic education needs to adopt an integrative epistemological model that combines revelatory principles, scientific rationality, and digital literacy as the basis for multicultural curriculum development. Such reconstruction is expected to strengthen the quality of Islamic education and prepare learners to be more critical, tolerant, and capable of participating in a pluralistic global society.